17-Week Delay Surgery after Chemoradiation in Rectal Cancer with Complete Pathological Response. (22nd October 2015) - Santos, Marisa D.; Gomes, Manuel T.; Moreno, Filipa; Rocha, Anabela; Lopes, Carlos
Abstract : Neoadjuvant chemoradiation (CRT) followed by curative surgery still remains the standard of care for locally advanced rectal cancer (LARC). The main purpose of this multimodal treatment is to achieve a complete pathological tumor response (ypCR), with better survival. The surgery delay after CRT completion seems to increase tumor response and ypCR rate. Usually, time intervals range from 8 to 12 weeks, but the maximum tumor regression may not be seen in rectal adenocarcinomas until several months after CRT. About this issue, we report a case of a 52-year-old man with LARC treated with neoadjuvant CRT who developed, one month after RT completion, an acute myocardial infarction. The need to increase the interval between CRT and surgery for 17 weeks allowed a curative surgery without morbidity and an unexpected complete tumor response in the resected specimen (given the parameters presented in pelvic magnetic resonance imaging (MRI) performed 11 weeks after radiotherapy completion).